Penerapan Metode Clustering Pada Penjualan Makanan Dan Minuman Dalam Menentukan Strategi Marketing - Evasaria Magdalena; Eufrasia Paskasius (Departemen Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2025)
Business competition including restaurant business is getting tighter with the change of business methods from conventional to online (digital). The problem is that the menu sold is not always comparable to the expenditure of raw materials purchased by the restaurant to make their food and beverage menus. Therefore, an appropriate marketing strategy is needed to be implemented. The restaurant used as the research material is the